Pre and post-liver transplant outcome of cirrhotic patients with acute on chronic liver failure. Issue 44 (30th October 2020) - Iacob, Speranta; Ghioca, Mihaela; Csiki, Irma Eva; Tomescu, Dana; Droc, Gabriela; Hrehoret, Doina; Brasoveanu, Vlad; Pietrareanu, Corina; Iacob, Razvan; Gheorghe, Cristian; Popescu, Irinel; Gheorghe, Liana
Abstract : Abstract: Acute on chronic liver failure (ACLF) is a dynamic syndrome, but frequently associated with a high 1 month mortality rate. This is the first study applying the new European Association for the Study of the Liver- chronic liver failure consortium criteria to explore mortality on the waiting list (WL) and early after liver transplantation (LT) in a cohort of Romanian cirrhotic patients that improved or recovered after an episode of ACLF. To assess frequency and waitlist mortality for different grades of ACLF. An observational study was conducted; 257 patients with liver cirrhosis included on the WL between 2015 and 2017 were analyzed. The cumulative incidence of waitlist mortality or removal was calculated for combination of competing events using multivariable competing risks regression. ACLF-1 occurred in 12.07%, ACLF-2 in 7.39% and ACLF-3 in 8.56% of patients. Median Model for End Stage Liver Diseases (MELD) score at the moment of ACLF was 29. The main event while on the WL was death, followed by ACLF; patients with ACLF-3 had a significantly greater subhazard ratio for mortality of 2.25 (1.55–3.26) compared to patients with ACLF-1 or 2. LT proved to be associated with a significantly lower risk of death on the WL at 6 months after inclusion. One and 12 months post-transplant survival of patients with or without ACLF was similar ( P = .77). Occurrence of an ACLF episode while on the WL is associated with a significantly high mortality rate, as well as MELD score at inclusion on the WL, renal and liver failure, presence of hepatic encephalopathy. Overall patient short and long term survival after LT is similar to non-ACLF patients in good selected cases.